A Possibility for Large-Scale Production of 238Pu in Light-Water Reactor VVER-1000 - Anatoly N. Shmelev; Nikolay I. Geraskin; Vladimir A. Apse; Vasily B. Glebov; Gennady G. Kulikov; Evgeny G. Kulikov (Journal of Nuclear Engineering, 2022)
This paper considers the possibility for large-scale production of plutonium isotope 238Pu in the light-water nuclear power reactor VVER-1000. 238Pu is a unique source of long-term autonomous energy supply in various devices for remote regions of the Earth and in outer space. The design of the irradiation device with 237NpO2 as a starting material is proposed, which is placed in the central zone of the VVER-1000 reactor core and makes it possible to achieve 8% of the specific Pu production (Pu/237Np) by optimizing the pitch of NpO2-rod lattice. The computations showed that the scale of 238Pu production in the irradiation device was remarkably larger (2 ÷ 7 times more) than similar values in research reactors. At the same time, the use of heavy neutron moderators with low neutron absorption (natural lead or lead isotope 208Pb) around the NpO2 fuel assembly (FA) made it possible to obtain high-purity 238Pu with the content of 236Pu below 2 ppm. The paper also shows that if the irradiation device is placed in central zone of the VVER-1000 reactor core, then the displacement damage dose in the reactor vessel remains low enough to conserve its strength properties throughout the entire period of the reactor operation (60 years).